Інформаційні технології обробки даних в ресторанному бізнесі - Євменкін, Д. К. (ХНУРЕ, 2024)
Information technologies for data processing is of paramount important in the development of the restaurant business to reduce costs and improve the service efficiency. In order to capture valuable information and make reasonable decisions, it is needed to collect, save, process and analyze a large amount of information. Data processing includes filtering, sorting, analysis and interpretation of data. At this stage, patterns, trends and connections for the adoption of priming solutions are revealed. Therefore, one of the important aspects of the data processing is considering errors of data. To this aim the Kaucher interval arithmetic is used in this study.
Keywords: обробка даних; ресторанний бізнес; інформаційні технології